Dairy Producers Who Market Their Surplus Progeny as Calves Use Germplasm With Slightly Lighter and Less-Conformed Carcasses Than Producers Who Rear Their Surplus Progeny Beyond Weaning - Berry, Donagh P.; Ring, Siobhan R. (Frontiers in Veterinary Science, 2021)
Understanding dairy producer mind-set in service sire selection can provide useful information for different junctures along the commercial and extension animal breeding chain. The objective of the present study was to examine if differences exist among dairy producers in their choice of dairy and beef service sires depending on the life stage at which the surplus progeny generated from such matings exit the dairy farm. The objective was accomplished through the cross-sectional analyses of progeny fate data from 1,092,403 progeny in 4,117 Irish dairy herds. Herd-years were categorized into one of four systems based on when the surplus progeny exited the dairy farm: 1) calves sold < 70 d of age, 2) cattle sold as yearlings between 250 and 450 days of age, 3) prime cattle sold for finishing (slaughtered between 8 and 120 days of exiting the dairy farm), or 4) prime cattle sold for immediate slaughter (i.e., slaughtered within 7 days of exiting the dairy farm). Of the beef service sires used in herds that sold their surplus progeny as calves, their mean predicted transmitting ability for carcass weight and carcass conformation score was just 2.00 kg and 0.11 scores (scale of 1 [poor] to 15 [excellent]) inferior to the beef service sires used in herds that sold their surplus progeny as prime cattle for immediate slaughter. Similar trends, albeit of smaller magnitude were evident when comparing the genetic merit of the dairy service sires used in those systems. Cows in herds that sold their surplus progeny as calves were genetically less likely to incur dystocia as well as to have lighter, less-conformed and leaner carcasses than cows in herds that sold their surplus progeny post-weaning. Hence, results from the present study suggest that diversity in herd strategy regarding when surplus progeny exit the herd influences service sire selection choices in respect of genetic merit for dystocia and carcass attributes. That said, the biological difference based on the current pool of available service sires is small relative to the dairy producers that sell their surplus progeny as young calves